1986
DOI: 10.1007/bf00633190
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitory prejunctional 5-HT1-like receptor in the isolated perfused rat kidney

Abstract: The present study has identified a receptor for 5-hydroxytryptamine (5-HT) which functions to inhibit the stimulus-induced release of [3H] noradrenaline following sympathetic periarterial nerve stimulation to the isolated perfused rat kidney. In addition to 5-HT (IC30 = 4.5 X 10(-8) mol/l), both 5-carboxamidotryptamine (IC30 = 8 X 10(-9) mol/l) and 5-methoxy-3-(1,2,3,6-tetrahydro-4-pyridinyl) indole (RU-24969, IC30 = 2.5 X 10(-7) mol/l) acted as agonists whereas 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Additionally, it is to be remarked that our findings with metergoline, taken individually, cannot provide any evidence on the site of action, as it is capable of blocking either the prejunctional (Charlton et al, 1986) or postjunctional Shoeffter & Hoyer, 1990;Sumner, 1991) effects of 5-HT and/or 5-CT in other vascular preparations.…”
Section: Systemic and Carotid Haemodynamic Changesmentioning
confidence: 68%
See 2 more Smart Citations
“…Additionally, it is to be remarked that our findings with metergoline, taken individually, cannot provide any evidence on the site of action, as it is capable of blocking either the prejunctional (Charlton et al, 1986) or postjunctional Shoeffter & Hoyer, 1990;Sumner, 1991) effects of 5-HT and/or 5-CT in other vascular preparations.…”
Section: Systemic and Carotid Haemodynamic Changesmentioning
confidence: 68%
“…In this respect, it is important to note that the responses to acetylcholine (0.003, 0.01, 0.03 and 0.1 jg min-) remained unaltered after sumatriptan (7 + 2, 14 + 5, 24 + 6 and 41 ± 5 ml min' I before and 9 ± 4, 14 ± 5, 24 ± 4 and 37 ± 4 ml min-' after sumatriptan, respectively). 5-MeO-T (pg min-') Figure 3 The effects of (a) physiological saline (0, 0 ml kg-'; 0, the prejunctional (Charlton et al, 1986) or postjunctional Schoeffter & Hoyer, 1990;Sumner, 1991) effects of 5-HT and/or 5-CT in other vascular preparations.…”
Section: Systemic Haemodynamic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although (-)-pindolol does not antagonize all of the effects considered to be mediated by 5-HT1-like receptors (Feniuk et al, 1983;Charlton et al, 1986), it does bind with high affinity to the putative 5-HTlA-and 5-HTlB-receptors and antagonizes functional responses thought to be mediated at these receptors (Middlemiss, 1984;Engel et al, 1986;Tricklebank et al, 1985;. Also, of greater relevance to the present study, Kennett et al (1987) have shown that (-)-pindolol and (±)-cyanopindolol antagonized the anorectic effects of the putative 5-HT1B-receptor agonist, RU24969.…”
Section: Discussionmentioning
confidence: 95%
“…With respect to the latter, several lines of pharmacological evidence have shown that 5-HT inhibits the contractile responses to adrenergic nerve stimulation in blood vessels by activation of prejunctional 5-HTl-like receptors; these blood vessels include, amongst others, the canine (Humphrey et al, 1988) and human ) saphenous veins; the canine common carotid (Mylecharane & Phillips, 1989), external carotid Villalon et al, 1993) and femoral (Feniuk et al, 1981) arterial beds; the rat kidney (Charlton et al, 1986) and vena cava (Molderings et al, 1987); and the porcine coronary artery (Molderings et al, 1989). 'Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%